Evaluation of the application of the Welfare Quality® audit protocol in Holstein cattle for fattening under desert conditions - Pérez-Linares, Cristina (2023)
The application of the European Welfare Quality® protocol was evaluated in finishing Holstein males in a fattening cattle production company located in the Mexicali Valley, Baja California, Mexico. Twelve pens were randomly selected with 75 steers per pen. In addition, 38 animals per pen were individually evaluated. The evaluation was performed using a format for each of the four principles: feeding, housing, health and behaviour, corresponding to 9 criteria and evaluating 20 measurements, to obtain a global rating. The results for the principles "good health" were 92 points, for housing " 88 points, for "health" 52 points and for " behaviour" 68 points. The overall rating was "good animal welfare". It is concluded that the European protocol WQ® is feasible to be applied in finishing feedlots; however, modifications and adaptations of some measurements are suggested in accordance with the climatic conditions of the area and the temperament of the Holstein cattle.